ANALISIS PERBANDINGAN PEMANFAATAN APBD POS BELANJA DI DAERAH PEMILIHAN PETAHANA DAN NON PETAHANA - Kustono, Alwan Sri; Pangestu, Wulan; Effendi, Rochman (School of Accountancy, University of Agung Podomoro, 2020)
This research aims to know the fairness level of significance increase on expenditure items inincumbent election area compare with non incumbent election area, and non-election area. Thisresearch use secondary data. Data analyze method use comparative description method which describethe result from our data observation that will be compared with one observation subject and otherobservation subject. The result shows that all of expenditure items not used as politicization object byincumbent. It’s because of increasing expenditure items trend not only occur on incumbent area, butalso on some non incumbent area and some non-election area. Significance increase on incumbent areacan not conclude as politicization budget and expenditure area by incumbent to preserve their power.